In-patient physiotherapy for adults on veno-venous extracorporeal membrane oxygenation – United Kingdom ECMO Physiotherapy Network: A consensus agreement for best practice. (August 2017) - Eden, Allaina; Purkiss, Claire; Cork, Gabriella; Baddeley, Adam; Morris, Kelly; Carey, Leah; Brown, Mike; McGarrigle, Laura; Kennedy, Samantha
Clinical specialist physiotherapists from the five severe respiratory failure centres in England where respiratory extracorporeal membrane oxygenation (ECMO) is practiced have established this consensus agreement for physiotherapy best practice. The severe respiratory failure centres are Wythenshawe Hospital, Manchester; Glenfield Hospital, Leicester; Papworth Hospital, Cambridge; Guy's and St Thomas' Hospital, London and The Royal Brompton Hospital, London. Although research into physiotherapy and ECMO is increasing, there is not a sufficient amount to write evidence-based guidelines; hence the development of a consensus document, using knowledge and experience of the specialist physiotherapists working with patients receiving ECMO. The document outlines safety aspects, practicalities and additional treatment considerations for physiotherapists conducting respiratory care and physical rehabilitation.